Dynamics of Social Accountability of Islamic Boarding School (Case Study of Pesantren Al-Hidayat Lasem) - Baihaqi, Jadzil; Mubarok, Husni (AKTSAR: Jurnal Akuntansi Syariah, 2024)
This study aims to explore the dynamic social accountability of Islamic boarding schools (Pesantren). This research is qualitative research using a case study paradigm focused on Pesantren Al-Hidayat Lasem. The dimensions of social accountability follow Ebrahim's (2003) concepts. Data are collected through in-depth interviews and observations. The informants of this research include the chief and administrator of Pesantren Al-Hidayat Lasem. Miles & Huberman Model is used to analyse the data, namely data reduction, data presentation, and concluding. The results of this study indicate that Pesantren Al-Hidayat has implemented financial reporting, performance evaluation, participation, and social audit.